2016
DOI: 10.1103/physrevlett.116.018101
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Oscillation in Self-Organized Critical States of Small Systems: Sensitive Resting State in Neural Systems

Abstract: Self-organized critical states (SOCs) and stochastic oscillations (SOs) are simultaneously observed in neural systems, which appears to be theoretically contradictory since SOCs are characterized by scale-free avalanche sizes but oscillations indicate typical scales. Here, we show that SOs can emerge in SOCs of small size systems due to temporal correlation between large avalanches at the finite-size cutoff, resulting from the accumulation-release process in SOCs. In contrast, the critical branching process wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…Besides, the moderately synchronized states also correspond to the oscillation onset (also indicated in Fig 2D , bottom inset), where the oscillation power goes through a clear transition from low to high as shown in Fig 3H . Therefore, neuronal avalanches and gamma oscillations emerge jointly, which is consistent with in vivo observations [ 8 , 40 ]. Specifically, neuronal avalanches are achieved by aggregating different groups of neurons into clusters at different time instants and sparsely synchronized oscillations emerge when the clusters are organized with typical time-scales.…”
Section: Resultssupporting
confidence: 89%
“…Besides, the moderately synchronized states also correspond to the oscillation onset (also indicated in Fig 2D , bottom inset), where the oscillation power goes through a clear transition from low to high as shown in Fig 3H . Therefore, neuronal avalanches and gamma oscillations emerge jointly, which is consistent with in vivo observations [ 8 , 40 ]. Specifically, neuronal avalanches are achieved by aggregating different groups of neurons into clusters at different time instants and sparsely synchronized oscillations emerge when the clusters are organized with typical time-scales.…”
Section: Resultssupporting
confidence: 89%
“…Our results confirmed that spike-based neuronal avalanches are likely to appear at a moderately synchronized firing state and can coexist with both irregular firing and stochastic oscillations. These observations might provide important biological implications, because the similar co-emergence of multi-scale cortical activities has been observed in both experimental and computational recordings (Gireesh & Plenz, 2008;S.-J. Wang, et al, 2016;Yang, et al, 2017;Yu, et al, 2011).…”
Section: Discussionsupporting
confidence: 56%
“…Previous work in in vitro and in rodents reported nested θ/β/γ–oscillations 63,64 embedded in avalanches. Simulations also demonstrate that oscillations can emerge during avalanches 65–68 . However, it had yet to be determined whether cortical avalanches in the awake mammal exhibit a distinct temporal profile that is scale-invariant, nor had it been known how that profile might relate to the scale of an oscillation.…”
Section: Discussionmentioning
confidence: 87%